Analisis Tingkat Efisiensi Dan Kinerja Keuangan Terhadap Efektivitas Pengelolaan Dana Kapitasi Jkn Berdasarkan Serapan Per Bulan Puskesmas Ngronggot Kabupaten Nganjuk Tahun 2018 - Yeni Widyawati (Universitas Islam Kadiri, 2020)
The general objective of this study is to identify how much the level of efficiency and effectiveness of JKN capitation fund management based on monthly absorption in Ngronggot Health Center Nganjuk Regency in 2018. The data used is absorption data or realization of expenditure per month in 2018. The basic principle of government financial management is how efficient and effective management that has been carried out so that achievement and absorption are high by utilizing available resources appropriately. In the application of financial performance the method used is the index number. This method will lead to the calculation of the financial performance of JKN Puskesmas Ngronggot capitation fund management. After obtaining the financial performance, the efficiency and effectiveness of the management of the JKN Puskesmas Ngronggot Capitation Fund will be calculated using the formula of efficiency analysis and effectiveness analysis. The results of the calculation of trend analysis using index numbers to show financial performance. The result is the financial performance of the management of the JKN Capitation Fund Ngronggot Health Center is in good condition, this is because in the realization of its spending the Ngronggot Health Center has increased and is stable. For efficiency analysis and effectiveness analysis it can be seen that efficiency has an average of 99.45% which can be said to be less efficient based on the Minister of Home Affairs criteria, while effectiveness has an average of 100.97% which can be said to be very effective based on the criteria of the Minister of Home Affairs.